2001
DOI: 10.1089/027245701750293493
|View full text |Cite
|
Sign up to set email alerts
|

An Antibody to p16INK4A Recognizes a Modified Form of Galectin-3

Abstract: Galectin-3 is a carbohydrate binding protein involved in multiple processes including cell-cycle regulation and apoptosis. The ability of galectin-3 to protect cells from apoptosis is dependent upon a region of the protein known as a BH-1 domain for its homology to the anti-apoptotic protein Bcl-2. Here, we show that a monoclonal antibody (MAb) to the human tumor suppressor protein p16INK4A recognizes a post-translationally modified form of human galectin-3. The modified form is detectable in only a subset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Timmermann et al (32) demonstrated that epithelial cells gained increased activity of beta-galactosidase that is associated with senescence and produced p16 protein with no normal suppressor function. The reexpression of this incomplete protein detected by immnohistochemical method may be explained (33). …”
Section: Discussionmentioning
confidence: 99%
“…Timmermann et al (32) demonstrated that epithelial cells gained increased activity of beta-galactosidase that is associated with senescence and produced p16 protein with no normal suppressor function. The reexpression of this incomplete protein detected by immnohistochemical method may be explained (33). …”
Section: Discussionmentioning
confidence: 99%